Submission Instructions - Rede de Direito Civil Contemporâneo (Revista de Direito Civil Contemporâneo, 2021)
The Journal of Contemporary Private Law, ISSN 2358‑1433, published quarterly by Editora Revista dos Tribunais, in Brazil, invites academics and researchers to submit unpublished papers for its first issue of 2015, in the following areas: a) jurisprudence related to private law; b) history of private law; c) roman law; d) comparative private law; e) the law of obligations; f) contracts; g) torts; h) property law; i) family law; j) Probate and Succession Law. [...].